A tawhidic paradigm approach on qualitative research in management - Mhd Sarif, Suhaimi; Zainudin, Dolhadi; Yahya, Rohaziah (World Academy of Islamic Management (WAIM), 2020)
A Tawhidic paradigm approach to qualitative research in management offers the worldview from the revelation that contains Divine Commandments. Qualitative research in management uses cross disciplinary studies to contribute to the body of knowledge in management. There have been realism, constructionism and pragmatism paradigms used in the research of management. By adding the research paradigm with Tawhidic paradigm provides alternative research paradigm although it has not been encouraging. This study obtained feedback through personal interview from qualitative social researchers pertaining to the inclination toward applying Tawhidic Paradigm. The respondents gave positive inclination on the application of Tawhidic Paradigm given the holistic, comprehensive and balanced ontology, epistemology and methodology.